Modeling of the Additional Channel of Feedback in Eye-Tracking and Neuro Computer Interfaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper analyzes the features of the application of the additional computer-human communication channel within the neuro computer (brain-computer) and oculographic interfaces. The mathematical model of the functioning of this channel and its influence on the decision making by the user, taking into account the change in the accuracy of the definition of the user-generated command, depending on the time of the process analysis, is developed. The model is based on the approach according to which when receiving information about the nature of signal processing by the hardware and software part of the interface; the user can change his / her state, which influences the further processing of the results. The numerical modeling for neuro computer and oculografic interfaces was carried out; the values of the time ranges during which the presentation of the information on the results of the preliminary classification of the user's commands can provide an improvement in the results of work. The obtained results allow optimizing the use of the developed technologies of the additional human-computer communication channel in the aspect of increasing the speed of their work.